The Influence of Work-Life Balance, Job Stress, and Leadership Style on Turnover Intention Among Employees at PT. Siantar Top Tbk - Krisna Rahmadani Pratama; Acep Samsudin (Lavish Opulent Education, 2025)
This study aims to analyze the effect of work-life balance, job stress, and leadership style on turnover intention among employees of PT. Siantar Top Tbk. Turnover intention is a critical issue for companies as it impacts productivity and organizational stability. Poor work-life balance, high levels of job stress, and an inappropriate leadership style can influence employees’ decisions to leave the company. This research employs a quantitative approach using multiple linear regression analysis to examine the relationships between variables. Data were collected through questionnaires distributed to employees of PT. Siantar Top Tbk. The results indicate that work-life balance has a positive effect on turnover intention, meaning that the worse the balance between work and personal life, the higher the employees’ intention to leave. Job stress has a positive effect on turnover intention, implying that higher stress levels increase employees' likelihood of resigning. Additionally, leadership style not influences turnover intention, where leadership style not effective can reduce employees' desire to leave. Simultaneously, work-life balance, job stress, and leadership style significantly affect turnover intention. Therefore, it is recommended that the company enhances employees' work-life balance, manages job stress effectively, and implements a more efficient leadership style to reduce turnover intention and improve employee retention.